Hypertension induced by antiangiogenic therapy: clinical and pathophysiological aspects. Issue 3 (12th April 2012) - van den Meiracker, Anton H; Lankhorst, Stephanie; van Esch, Joep HM; Jan Danser, AH; Kappers, Mariëtte HW
Abstract : Angiogenesis inhibition with humanised monoclonal antibodies to vascular endothelial growth factor (VEGF) or with VEGF receptor tyrosine kinase inhibitors targeting VEGF receptors has become an established treatment for various forms of cancer. Unfortunately, inhibition of the VEGF pathway is associated with serious side effects including hypertension. The development of this hypertension is likely to be multifactorial with a major role of the endothelin system. Although initially considered as a toxic effect, the development of hypertension may predict a favourable antitumour response. As a consequence, hypertension should not be a reason for dose reduction or discontinuation of antiangiogenic therapy but should be treated with antihypertensive therapy according to existing guidelines.